The effect of periodization and training intensity distribution on middle- and long-distance running performance: A systematic review - Kenneally, M.; Casado, A.; Santos-Concejero, J. (International Journal of Sports Physiology and Performance, 2018)
This review aimed to examine the current evidence for 3 primary training intensity distribution types: (1) pyramidal training, (2) polarized training, and (3) threshold training. Where possible, the training intensity zones relative to the goal race pace, rather than physiological or subjective variables, were calculated. Three electronic databases (PubMed, Scopus, and Web of Science) were searched in May 2017 for original research articles. After analysis of 493 resultant original articles, studies were included if they met the following criteria: (1) Their participants were middle- or long-distance runners; (2) they analyzed training intensity distribution in the form of observational reports, case studies, or interventions; (3) they were published in peer-reviewed journals; and (4) they analyzed training programs with a duration of 4 wk or longer. Sixteen studies met the inclusion criteria, which included 6 observational reports, 3 case studies, 6 interventions, and 1 review. According to the results of this analysis, pyramidal and polarized training are more effective than threshold training, although the latest is used by some of the best marathon runners in the world. Despite this apparent contradictory finding, this review presents evidence for the organization of training into zones based on a percentage of goal race pace, which allows for different periodization types to be compatible. This approach requires further development to assess whether specific percentages above and below race pace are key to inducing optimal changes.